Analisis Panel Data Web Scraping Artikel Kekerasan Dalam Rumah Tangga Tahun 2019- 2020 di DKI Jakarta - Dameani, Tiara (JURNAL TEKNOLOGI INFORMASI, 2021)
Domestic Violence is a crime by individuals that occurs in a small scope and by people known to the victim. In this study, data on Domestic Violence was obtained using the web scraping method for articles in online media for 2019-2020 in five cities in DKI Jakarta Province. In addition to scraping data, this study also uses two additional data sources (1) the National Socio-Economic Survey data in measuring the level of alcohol consumption and the average price of alcohol in cities in Jakarta. (2) Official publication data on the website of the Central Bureau of Statistics in measuring the unemployment rate and per capita expenditure. The results of this study (1) Describe how to scrap online media using the Kapow application (2) Modeling data panel Pooled Least Square relationship of domestic violence with the environment at the city level. The conclusions of this study are (1) that with the web scraping method researchers can easily get data and are more real time than having to wait for official court reports, (2) alcohol consumption, prices, unemployment rates, per capita expenditures do not identify an effect on Internal Violence. Bulk stairs, this may be caused by psychological factors rather than environmental factors. Suggestions for further research are to further expand the factors that cause domestic violence and expand the panel data period which is not only limited to two periods.